2020
DOI: 10.1016/j.carbon.2020.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of highly water dispersible few-layer graphene in vivo

Abstract: In the last decade, graphene-based materials have received increasing attention for both academic research and industrial uses. However, products containing graphene must meet the same standards for quality, safety and efficacy as products not containing nanomaterials. Our aim is to shed light on the toxicological characterization of few-layer graphene (FLG) dispersions. In the present study, graphene was easily dispersed in water using biocompatible riboflavin-5′-phosphate sodium salt (Rib). A highly concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…[ 132,167 ] In these, water molecules can pass through the narrow hydrophobic channels formed by the unoxidized regions of GO. [ 168 ] The rejection of ions or bigger molecules takes place mainly for size exclusion as these cannot pass between the stacked GO flakes, yet anions can also be rejected by electrostatic interactions. [ 169 ] However, over time GO membranes tend to lose the semipermeability as a result of the increase in the interlayer spacing between flakes.…”
Section: Application Of Hybrid Assembly Based On Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…[ 132,167 ] In these, water molecules can pass through the narrow hydrophobic channels formed by the unoxidized regions of GO. [ 168 ] The rejection of ions or bigger molecules takes place mainly for size exclusion as these cannot pass between the stacked GO flakes, yet anions can also be rejected by electrostatic interactions. [ 169 ] However, over time GO membranes tend to lose the semipermeability as a result of the increase in the interlayer spacing between flakes.…”
Section: Application Of Hybrid Assembly Based On Graphenementioning
confidence: 99%
“…Many studies about the toxicity of graphene have been performed; still, notably different results have been reported, mainly because of the high diversity between the available graphene types, e.g., in size and chemical composition. [ 134b,168 ] Furthermore, the functionalization of graphene surface can greatly modify its toxicity. Pristine graphene is highly hydrophobic; thus, it has found limited application in the biomedical field.…”
Section: Application Of Hybrid Assembly Based On Graphenementioning
confidence: 99%
“…[55] We also found high cell viability of RAW 264.7 cells after exposure to FLG for 24 h and no in vivo hematotoxicity in Balb/c mice at 300 µg/mouse up to 30 days. [56] Recently, Cristo et al presented the detailed toxicity mechanism of low-dose (2.5 and 5 µg/cm 2 ) of 265 nm FLG in RAW 264.7 macrophages. The results of this study revealed that FLG induced inflammation by oxidative stress, triggering endoplasmic reticulum stress-mediated autophagy.…”
Section: Graphenementioning
confidence: 99%
“…34 Interestingly, FMN has the effect of reducing the toxicity profile of graphene, a serious concern with graphene use, 35,36 likely due to reduced graphene agglomeration which could further promote its use in biomedical devices. 37 With these properties in mind, a graphene was sought with the advantages of both liquid exfoliated graphene and ballmilled graphene, by ball-milling graphite in the presence of the surfactant FMN, followed by the removal of any non-covalently bonded FMN by dialysis. The FMN covalently bonded to graphene increased processability, while the synthesis is environmentally friendly and readily scalable.…”
Section: Introductionmentioning
confidence: 99%
“…34 Interestingly, FMN has the effect of reducing the toxicity profile of graphene, a serious concern with graphene use, 35,36 likely due to reduced graphene agglomeration which could further promote its use in biomedical devices. 37…”
Section: Introductionmentioning
confidence: 99%